EVALUASI KESESUAIAN LAHAN DAN UPAYA PENGEMBANGAN LAHAN KERING UNTUK BUDIDAYA TANAMAN TEBU DI KABUPATEN BREBES - Mulyono, Daru (Jurnal Rekayasa Lingkungan)
The objectives of the research is to obtain upland data and information especially for extensifi cation of sugarcane development through optimal land fertilization. Furthermore, the impacts of this action are to increase the planting area of sugarcane and productivity. The research use Geographical Information System (GIS) in Brebes Regency, starting from June until October 2007 and the field survey was done at the end of August 2007. The results of the research showed that the suitable, conditionally suitable, and not suitable land for sugarcane cultivation in Brebes Regency reach to a high of 40,148 ha, 7,555 ha, and 124,071 ha respectively. The potential upland for sugarcane cultivation reach to a high of 38,264 ha. Based on the soil condition with low contents of N, P and K, the recommended dosage calculation of N, P, and K fertilizers for optimal sugarcane cultivation reach to a high of: N (ZA) = 575 kg/ha, P (SP-36) = 170 kg/ha, and K (KCl) = 600 kg/ha.Key words : sugarcane, upland for sugarcane